2000
DOI: 10.1046/j.1365-2141.2000.02474.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetically cryptic AML1-ETO and CBFbeta-MYH11 gene rearrangements: incidence in 412 cases of acute myeloid leukaemia

Abstract: The rearrangements t(8;21)(q22;22) and inv(16)(p13q22) are two of the most frequently seen in acute myeloid leukaemia (AML), accounting for 8% and 4% of cases respectively. Detection of these abnormalities is important for disease management as both are associated with good responses to conventional chemotherapy and prolonged disease-free survival. Recent reports using reverse transcriptase polymerase chain reaction (RT-PCR) suggest that significant proportions of AML cases without a visible t(8;21) or inv(16)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
33
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 26 publications
2
33
1
Order By: Relevance
“…166 The inv(16)-positive AMLs are included with those with t(8;21) translocation in a group generally referred to as 'core binding factor' (CBF) leukemias, as both are characterized by rearrangements of genes that code for components of the heterodimeric transcription factor CBF, which plays an essential role in hematopoiesis. 167 Inv(16) or the rarer t(16;16)(p13;q22) leads to fusion of the CBFB chain gene with the smooth muscle myosin heavy chain gene MYH11.…”
Section: Introductionmentioning
confidence: 99%
“…166 The inv(16)-positive AMLs are included with those with t(8;21) translocation in a group generally referred to as 'core binding factor' (CBF) leukemias, as both are characterized by rearrangements of genes that code for components of the heterodimeric transcription factor CBF, which plays an essential role in hematopoiesis. 167 Inv(16) or the rarer t(16;16)(p13;q22) leads to fusion of the CBFB chain gene with the smooth muscle myosin heavy chain gene MYH11.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Both types of disease are referred to collectively as core binding factor (CBF) leukemias resulting in the rearrangement, respectively, of alpha (CBFalfa or AML1) or beta (CBFbeta) subunits of the same transcription factor CBF which plays a key role in hematopoiesis. 4 In particular, genomic rearrangements in t (8;21) and inv (16) leukemias fuse CBFalfa with the gene encoding the ETO transcription factor and CBFbeta with the smooth muscle myosin heavy chain gene MYH11, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…However, by analogy, analysis of 186 consecutive patients with PML-RAR␣-positive acute promyelocytic leukemia (APL) entered into the UK Medical Research Council (MRC) ATRA trial showed that 15% lack the t(15;17) due to cytogenetic failures (9%), insertions (4%) or more complex rearrangements (2%), 18 which is in accordance with data from the European Working Party. 19 As exemplified by the reports by Rowe et al 20 and Sarriera et al, 21 studies evaluating the role of molecular screening in AML to date have reported differing rates of detection of AML1-ETO and CBF␤-MYH11 in cases lacking the classic t(8;21) or inv(16)/t(16;16), respectively (see Tables 1 and 2 it should be born in mind that the studies detailed in Tables 1 and 2 are relatively small. This precludes reliable determination of the precise frequency of cryptic CBF gene rearrangements in AML and raises the possibility that the observed differences may in some instances have arisen by chance.…”
mentioning
confidence: 51%
“…The studies reported by Rowe et al 20 and Sarriera et al 21 raise a number of key issues. In particular, they highlight the importance of confirming detection of leukemia-associated fusion genes revealed by RT-PCR screening with an independent technique.…”
mentioning
confidence: 99%
See 1 more Smart Citation